Management of Virtual Reality Application Usage: A Comparison of Usability and Immersiveness through Controller-Based and Hand Gesture Interaction Methods - Bianca Pingkan Nevista; Herman Tolle; Fitra A. Bachtiar (Optima Science, 2025)
Natural User Interface (NUI) is a latest development in the world of human-computer interaction can applied to immersive digital technology and realized in virtual reality. This virtual reality (VR) is usually accessed using a VR headset, so there are several companies that develop and improve VR headsets to facilitate interaction between humans and computers. One of the VR headsets available for beginners and professionals is the Meta Quest 2 which can be used with two interaction methods, namely, controllers and hand gesture. This study was conducted to compare the usability and immersivity of the two interaction methods on the Meta Quest 2 VR headset. This test was conducted at a Vocational High School in Malang, one of the city in Jawa Timur, in the Visual Communication Design Departement who had never used a VR headset before. There are two methods used, namely, Usability Testing to measure usability and the Igroup Presence Questionnaire (IPQ) method is used to measure immersivity. The applications used in this study are the Waltz of The Wizard Game, The Walking Dead Game: Saints & Sinners and Virtual Reality-Based Applications as Educational Media for Cultural Heritage Buildings in Malang City. The results of the usability and immersiveness tests show that in the Waltz of The Wizard game, it gets a high coefficient value on hand gestures, which is 0.136 and 0.096 on the controller. While in the game The Walking Dead: Saints & Sinners, it gets a high coefficient value on the controller, which is 0.398 and 0.171 on hand gestures. And in the Cultural Heritage Application, it gets a high coefficient value on hand gestures, which is 0.065 and 0.055 on the controller. From the coefficient values, usability and immersivity in the use of controllers are higher in action genre applications, for example the game The Walking Dead: Saints & Sinners. While in hand gestures, usability and immersivity are high when using adventure genre applications, for example the Waltz of The Wizard game and exploration, for example the Cultural Heritage Application game. This means that the interaction method and type of application used determine the level of usability and immersivity.